Strategies for Responding to Academic and Workplace Challenges in Islamic Higher Education - Sulton, Ahmad (Edukasia Islamika : Jurnal Pendidikan Islam, 2024)
This research responds to the increasing number of unemployed graduates of Islamic universities including IAIN Ponorogo. Improvement efforts are always made as a step to continuously improve the quality of graduates so that they are able to master and apply science and technology in line with the challenges of the times. The study aims to explore the role of the integration of faith, science, and charity as a guideline for scientific and institutional development at IAIN Ponorogo in the paradigm of market orientation versus humanism. Qualitative research approach, data collection was conducted through observation techniques, in-depth interviews, and document analysis. Data analysis was conducted by data reduction, presentation, and conclusion drawing. The findings of this study; first, the reactualization of the integration of faith, science and charity as the development paradigm of IAIN Ponorogo is considered important and strategic after the institutional transformation from STAIN to IAIN 2016. IAIN Ponorogo did not have a scientific paradigm previously, so it was considered ineffective enough to guide the future development of IAIN Ponorogo. Second, the formulation of the paradigm of integration of the concepts of faith, science and charity is by positioning tawhid as the foundation in interpreting all forms of science. Science cannot be separated from Allah SWT, science must function to get closer to the Creator and encourage good deeds. Third, the response of the academic community of IAIN Ponorogo to the paradigm of integration of faith, science, and charity includes scientific works in the form of books and journal articles, verbal responses in discussion groups. The socialization and internalization of the integration of faith, science, and charity to the entire academic community of IAIN Ponorogo in its various forms needs to be continuously improved.